UJI AKTIVITAS ANTIOKSIDAN FRAKSI n-HEKSAN EKSTRAK ETANOL DAUN KARIKA (Carica pubescens) DAN IDENTIFIKASI SENYAWA ALKALOID DAN FLAVONOIDNYA - Annis Mu’awwanah; Maria Ulfah (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Free radicals can lead to various dangerous diseases, such as cancer. Active compounds from medicinal plants such as flavonoids and alkaloids have been shown the antioxidant effects and may serve to prevent the negative effects of free radicals. Two of these compounds have been identified in leaf extract (Carica pubescens) and can be separated from other compounds with fractionation method. The purpose of this study was to determine the antioxidant activity of n-hexane fraction of karika leaves ethanol extract (HFKLEE) with DPPH method and identify its alkaloids and flavonoids compounds. Antioxidant activity of HFKLEE series concentration (50; 100; 150; 200; 250 and 300) ppm was performed by the DPPH method. Vitamin C series concentration (0.5; 1.0; 1.5; 2.0 and 2.5) ppm was used as a standard solution. Identification of alkaloids and flavonoids compound in HFKLEE determined by the thin layer chromatography (TLC) method. The results showed that HFKLEE has antioxidant activity with IC50 values of 157.134 ppm and Vitamin C at 2.875 ppm. TLC results indicate the presence of alkaloids and flavonoids compounds in HFKLEE. Key words: Karika leaves (Carica pubescens), n-hexane fraction, antioxidant, flavonoids and alkaloids